Excellent performance supercapacitors with the compounding of Ni(OH)2 and ZIF-67 derived Co–C–N nanosheets as flexible electrode materials. Issue 20 (21st September 2022) - Li, Dequan; Shen, Congcong; Lu, Qiang; Yan, Ruihan; Xiao, Bin; Zi, Baoye; Zhang, Jin; Lu, Qingjie; Liu, Qingju
Abstract : A unique composite structure consists of ZIF-67 derived Co–C–N nanosheets and Ni(OH)2 nanoparticles was successfully prepared on the carbon cloth, the optimum electrode material exhibits an ultrahigh specific capacitance of 2100 F g −1 in 1 A g −1 . Abstract : Owing to the advantages of high theoretical capacity, low cost, and excellent chemical stability, Ni(OH)2 is considered as a potential candidate for electrode materials of supercapacitors. However, its further applications are limited by its adverse surface chemical properties. In this paper, a composite material consisting of ZIF-67 derived Co–C–N nanosheets and Ni(OH)2 was synthesized facilely on carbon cloth in situ, and based on the collective advantages of the various components, excellent electrochemical performance could be achieved when used as a flexible electrode material of supercapacitors. In detail, the as-obtained sample Ni(OH)2 /Co–C–N/CC exhibits an ultrahigh specific capacitance of 2100 F g −1 at a current density of 1 A g −1 . Moreover, the further assembled asymmetric supercapacitor device exhibits a maximum energy density of 78.6 W h kg −1 at a power density of 749.4 W kg −1 . Furthermore, the device also shows outstanding cycling stability with 90.2% capacitance retention after 5000 cycles of charge–discharge. Basically, the remarkable performance can be attributed to the well-developed structure, abundant active sites, complex beneficial components, and their intrinsic properties. Significantly, rational design can broaden the research directions of corresponding electrode materials.